Understanding The Plurality Of Consumer Dispute Resolution In Indonesia: A Comparative Study With Singapore - Anita Afriana; Efa Laela Fakhriah (Yuridika, 2019)
Globalization has impacted many aspects of human life. It accelerates trade transactions between producers and consumers. Despite of numerous advantageous it brings, globalization also has a potential to cause various disadvantageous and loss to the consumers that ultimately lead to consumer disputes. In general, consumer disputes involve small amount of loss and complaint filed by the consumers for material compensation. In Indonesia, consumer dispute resolution is carried out not only by the Consumer Dispute Settlement Body (BPSK) but also through the courts. Recently, there are many newly-established consumer dispute settlement institutions. This article is part of a completed study discussing a plurality of consumer dispute settlement in Indonesia and a comparative analysis with the one available in Singapore. The study applies normative juridical research method and qualitative juridical analysis, it can be concluded that the plurality of consumer dispute settlement in Indonesia has led to convoluted mechanisms and procedures in settling disputes. This leads to a lack of legal certainty. The comparative law study being the instrument of this study is a critical instrument in the framework of legal reformation. Result shows that in Singapore, consumer disputes are resolved by a Small Claims Procedure method on State Court and through CASE as a private nonlitigation agency with specific consumer characteristics and disputes.